أثر عدم التأكّد البيئي المدرك على مستوى تطوّر نظم معلومات المحاسبة الإداريّة - دراسة تجريبيّة مقارنة بين بيئات خدميّة وصناعيّة في سوريا: The Impact of Perceived Environmental Uncertainty on Management Accounting Information Systems Sophistication Level – A Comparative Empirical Study between Service and Industrial Environments in Syria - ربى عباس علي, (Journal of North African Economies, 2025)
This research examines the impact of Perceived Environmental Uncertainty (PEU) on Management Accounting Information Systems (MAIS) Sophistication Level in two environments (Service & Industrial) in Syria, and compares whether there are statistically significant differences in the impact of PEU on MAIS Sophistication Level between the two environments. Based on a questionnaire survey conducted with 106 managers (54 managers work in service companies & 52 managers work in industrial companies), a Comparative Empirical Approach was used, and the Data were analyzed and Hypotheses tested by Simple Regression and Mann-Whitney U Test for independent samples using SPSS V.27. The findings emphasize that there is a positive and significant impact of PEU on MAIS Sophistication Level in both environments, with statistically significant differences in the impact of PEU on MAIS Sophistication Level between the two environments, in favor of Service environment. Mann-Whitney U analysis also emphasizes that MAIS Sophistication Level in Service environment is more sophisticated than MAIS in Industrial environment, and the Managers' PEU in a Service environment is higher than in an Industrial environment. Key words: MAIS Sophistication Level, Comparative Empirical Approach, Mann-Whitney U, Service, Industrial.